Modelling of an age-structured population dynamics taking into account a discrete set of offspring - Skakauskas, Vladas; Repšys, Šarūnas (Lietuvos matematikos rinkinys, 2016)
A model for description of an age-structured population dynamics taking into account a discrete set of offspring, their care, and spatial diffusion in two-dimensional space is studied numerically. The model consists of a coupled system of integro-partial differential equations. Some results are illustrated by figures.